A continuous preparation method for bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement

By growing bamboo-shaped carbon nanotubes on the surface of carbon fibers, using copper and sulfur catalysts, the problems of poor quality, low yield and uneven distribution of carbon nanotubes in the prior art are solved, and a high-performance carbon fiber composite material is realized.

CN116556048BActive Publication Date: 2025-03-14SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310664551.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2025-03-14
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

The prior art is difficult to take into account high-quality carbon nanotubes, low amorphous carbon impurities, high carbon nanotube yield and uniform distribution, resulting in poor interface bonding effect of carbon fiber composite materials.

Method used

Using copper as the main body and sulfur as the accelerator, bamboo-like carbon nanotubes were successfully grown on the surface of the carbon fiber by electrochemical treatment, thermal reduction and chemical vapor deposition, forming a continuous high-quality multi-scale reinforcement body.

Benefits of technology

The high interface performance and excellent tensile properties of carbon fiber composite materials have been achieved, and the problems of unstable structure, uneven distribution, and difficult to take into account both high yield and associated impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116556048B_ABST
    Figure CN116556048B_ABST
Patent Text Reader

Abstract

The invention discloses a continuous preparation method of a bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement, wherein the continuous carbon fiber without pulp is subjected to electrochemical treatment, then continuously impregnated with a mixed solution containing copper salt and sulfur source and dried, and then the fiber is subjected to thermal reduction treatment in a tubular furnace filled with hydrogen, and finally the fiber is passed through a tubular furnace filled with hydrogen and carbon source to grow bamboo-shaped carbon nanotubes, and is continuously collected using a wire collecting machine to obtain a bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement. A new catalyst combining a sulfur accelerator and a copper catalyst is used to grow a uniformly distributed, high-quality bamboo-shaped carbon nanotube structure with a high yield on the surface of the carbon fiber, while the associated amorphous carbon impurities and fragile carbon nanowires are significantly reduced, and the composite material prepared using the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement has excellent interface properties and tensile properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber surface modification, and in particular relates to a method for continuously preparing a bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Carbon fiber reinforced composite materials are one of the most promising emerging materials. They have been booming in the fields of military equipment, aerospace, sports goods, industrial equipment, infrastructure, ships and vehicles, and are also valued in the fields of new energy. In order to give full play to the role of reinforcement in composite materials and enable the load to be effectively transferred to the carbon fiber, it is of great significance to modify the smooth carbon fiber surface. Among them, multi-scale reinforcements have strong interface bonding potential and are considered to be one of the most effective surface modification methods. Carbon nanotubes and carbon fibers are both graphite sheet structures with high strength and good compatibility. Growing carbon nanotubes on the surface of carbon fibers has become one of the most popular multi-scale reinforcement preparation methods.

[0004] However, the continuous carbon nanotube-carbon fiber multi-scale reinforcement prepared by the existing technology is difficult to take into account the requirements of higher quality carbon nanotubes, less amorphous carbon impurities, higher carbon nanotube yield and uniform carbon nanotube distribution, making it difficult to further exert the multi-scale reinforcement effect of the composite material interface. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a continuous preparation method of a bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement, that is, a continuous preparation method for growing carbon nanotubes on the surface of carbon fiber, wherein the grown carbon nanotubes generally have a high degree of graphitization and a bamboo-shaped microstructure, and the bamboo-shaped carbon nanotubes can evenly wrap the surface of the carbon fiber. The method is based on a nanoparticle catalyst with copper as the main body and sulfur as the promoter. The bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared by this method has higher interface performance than the products of the prior art, can effectively improve the interface bonding ability of the composite material, and the tensile performance is also relatively excellent. The preparation method of the present invention can effectively solve the problems of unstable structure and uneven distribution of carbon nanotubes in the carbon nanotube-carbon fiber multi-scale reinforcement prepared by the prior art, and it is difficult to balance high yield and associated impurities.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for continuously preparing a bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement, comprising:

[0008] The continuous carbon fibers are electrochemically treated to obtain surface activated carbon fibers;

[0009] The surface-activated carbon fibers are continuously introduced into a mixed solution containing a copper salt and a sulfur source, followed by drying to obtain continuous carbon fibers with the copper salt and the sulfur source loaded on the surface;

[0010] The continuous carbon fiber with copper salt and sulfur source loaded on the surface is subjected to thermal reduction treatment in a first tubular furnace filled with hydrogen to form a copper-sulfur catalyst in situ on the surface of the carbon fiber, thereby obtaining a continuous carbon fiber loaded with the copper-sulfur catalyst;

[0011] The continuous carbon fiber loaded with copper-sulfur catalyst is passed through a second tubular furnace filled with hydrogen and a carbon source, and bamboo-shaped carbon nanotubes are in situ grown on the surface of the carbon fiber by chemical vapor deposition.

[0012] In a second aspect, the present invention provides a continuous bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared by the preparation method described in the first aspect.

[0013] In a third aspect, the present invention provides a composite material, which comprises the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement described in the second aspect.

[0014] In a fourth aspect, the present invention provides applications of the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement described in the second aspect or the composite material described in the third aspect in the preparation of military equipment, aerospace, sporting goods, industrial equipment, infrastructure, ships and vehicles, and new energy components.

[0015] One or more of the above technical solutions have the following beneficial effects:

[0016] 1. The present invention can make more bamboo-like carbon nanotubes grow evenly on the surface of carbon fiber, while producing very few amorphous carbon impurities and fragile carbon nanowires, thereby stably preparing continuous high-quality bamboo-like carbon nanotube-carbon fiber multi-scale reinforcement;

[0017] 2. The bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared by the present invention can significantly enhance the interface performance of carbon fiber composite materials and has good tensile properties;

[0018] 3. The present invention adopts an improved sulfur-containing copper catalyst, which has good compatibility with the existing process, does not involve additional equipment and devices, and is easy to operate; the preparation method can be carried out continuously throughout the whole process and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1 A is a scanning electron microscope image of the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared in the present invention. Figure 1 B is a high-resolution transmission electron microscopy image of the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared in the present invention.

[0021] Figure 2 A is a high-resolution transmission electron microscopy image of the multi-scale reinforcement prepared in Example 1. Figure 2 B is a high-resolution transmission electron microscopy image of the multi-scale reinforcement prepared in Comparative Example 1. Figure 2 C is a high-resolution transmission electron microscopy image of the multi-scale reinforcement prepared in Comparative Example 2. DETAILED DESCRIPTION

[0022] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0023] Multi-scale reinforcements are formed by constructing a variety of microstructures on the surface of carbon fibers. These microstructures are usually nanoscale, which effectively increase the surface roughness of the fibers while forming a bridging effect between the fibers and the resin, thereby greatly enhancing the bonding effect of the interface.

[0024] The currently published continuous preparation process of carbon nanotube-carbon fiber multi-scale reinforcement has the problem of difficulty in controlling the quality of the obtained carbon nanotubes. The carbon nanotubes grown on the surface of carbon fiber are often loose and fragile, containing more non-tubular carbon nanowires and amorphous carbon clusters and other microstructures with weak shear resistance, which leads to weak reinforcement effect of the interface at the microscale. These micro-reinforcement phases with poor structural regularity are difficult to withstand the shear stress at the interface, so they often disintegrate prematurely and fail to play a bridging role. On the other hand, the process method that can grow high-quality carbon nanotubes and reduce the output of amorphous carbon impurities is difficult to be satisfactory in terms of catalytic efficiency. In the continuous process, the carbon nanotubes on the surface of the carbon fiber often grow unevenly, which ultimately leads to more concentrated stress in the weak points of the composite material.

[0025] As introduced in the background technology, in order to solve the problems of poor quality, low yield, uneven distribution and many associated amorphous carbon impurities of carbon nanotubes in carbon nanotube-carbon fiber multi-scale reinforcements in the prior art, the present invention provides a continuous preparation method for growing bamboo-like carbon nanotubes on the surface of carbon fiber, as well as continuous bamboo-like carbon nanotube-carbon fiber multi-scale reinforcements and composite materials thereof prepared by the method.

[0026] Therefore, the present invention proposes a continuous preparation method of a bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement, and the continuous preparation method comprises the following steps:

[0027] The slurry-free continuous carbon fibers are electrochemically treated, then continuously impregnated with a mixed solution containing a copper salt and a sulfur source and dried. Next, the fibers are passed through a tubular furnace filled with hydrogen for thermal reduction treatment. Finally, the fibers are passed through a tubular furnace filled with hydrogen and a carbon source to grow bamboo-like carbon nanotubes, and are continuously collected using a wire collector.

[0028] The present invention is further described below in conjunction with specific embodiments.

[0029] A typical embodiment of the present invention provides a continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement, comprising:

[0030] The continuous carbon fibers are electrochemically treated to obtain surface activated carbon fibers;

[0031] The surface-activated carbon fibers are continuously introduced into a mixed solution containing a copper salt and a sulfur source, followed by drying to obtain continuous carbon fibers with the copper salt and the sulfur source loaded on the surface;

[0032] The continuous carbon fiber with copper salt and sulfur source loaded on the surface is subjected to thermal reduction treatment in a first tubular furnace filled with hydrogen to form a copper-sulfur catalyst in situ on the surface of the carbon fiber, thereby obtaining a continuous carbon fiber loaded with the copper-sulfur catalyst;

[0033] The continuous carbon fiber loaded with copper-sulfur catalyst is passed through a second tubular furnace filled with hydrogen and a carbon source, and bamboo-shaped carbon nanotubes are in situ grown on the surface of the carbon fiber by chemical vapor deposition.

[0034] Among them, the use of copper catalyst can avoid the generation of amorphous carbon impurities and ensure the stable preparation of bamboo-shaped carbon nanotubes; the use of sulfur promoter can effectively improve the catalytic efficiency of the catalyst.

[0035] The temperature and air flow during the CVD process should also be adjusted according to the optimized values. Too low a growth temperature will also result in the failure to form bamboo-shaped carbon nanotubes; too high a growth temperature will seriously damage the strength of the carbon fiber.

[0036] In some examples of this embodiment, the continuous carbon fiber is pulp-free or de-slurried commercial carbon fiber, the number of monofilaments in the commercial carbon fiber tow is 1K, 3K, 6K or 12K, and the specification of the commercial carbon fiber is T300, T700 or T800.

[0037] In some examples of this embodiment, the electrochemical treatment is continuously carried out in an electrolytic cell with a graphite electrode as a cathode, continuous carbon fiber as an anode, and diammonium phosphate solution as an electrolyte.

[0038] In some examples of this embodiment, the electrolyte used in the electrochemical treatment is a 3-8 wt.% deionized aqueous solution of ammonium dihydrogen phosphate, the current intensity is 0.1-0.5 A, and the continuous carbon fiber passes through the electrolytic cell for 50-200 s.

[0039] In some examples of this embodiment, the copper salt is copper chloride or copper nitrate; the sulfur source is thiourea or thiophene; the solvent of the mixed solution is deionized water, ethanol or acetone;

[0040] Furthermore, the main component copper and the promoter sulfur in the copper-sulfur catalyst should have appropriate contents and proportions, and the concentration of copper ions in the mixed solution is 0.02-0.08 mol / L, and the concentration of sulfur atoms is 0.01-0.05 mol / L.

[0041] In some embodiments of this implementation, both sides of the first tubular furnace are open to allow carbon fibers to continuously pass through the furnace, and nitrogen gas flow is used at both ends of the first tubular furnace to block air outside the furnace, and a mixed flow of nitrogen and hydrogen is filled inside the furnace;

[0042] Furthermore, the temperature of the first tube furnace is set to 200-500°C, and the flow ratio of nitrogen and hydrogen in the furnace is 0-3:1.

[0043] In some embodiments of this implementation, the second tube furnace is open at both sides to allow the carbon fibers to continuously pass through the furnace, and nitrogen gas is used at both ends of the second tube furnace to block the air outside the furnace, and the interior is filled with a mixed gas flow of nitrogen, hydrogen and a carbon source; the carbon source is any one or more of methane, acetylene, carbon monoxide or gaseous ethanol;

[0044] Furthermore, the temperature of the second tube furnace is set to 500-700°C, the carbon source is acetylene, and the flow ratio of nitrogen, hydrogen and acetylene in the furnace is 0-6:0.5-3:1.

[0045] Another embodiment of the present invention provides a continuous bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared by the preparation method described in the first aspect.

[0046] Another embodiment of the present invention provides a composite material, which comprises the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement described in the second aspect.

[0047] Another embodiment of the present invention provides the application of the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement described in the second aspect or the composite material described in the third aspect in the preparation of military equipment, aerospace, sporting goods, industrial equipment, infrastructure, ships and vehicles, and new energy components.

[0048] Example 1

[0049] A continuous device is used to grow bamboo-like carbon nanotubes on the surface of pulp-free carbon fiber. In the following continuous steps, the traveling speed of the carbon fiber tow is set to 15 cm / min;

[0050] Step 1: The de-sized T700 carbon fiber is sent into the electrolytic cell, with a 5wt.% diammonium phosphate solution as the electrolyte, a graphite plate as the cathode, and a carbon fiber tow parallel to the graphite plate as the anode. The current intensity is 0.2A, and the carbon fiber passes through the cell for 160s. After passing through the electrolytic cell, the fiber enters the clean water tank for washing, and then is dried in a 75°C oven;

[0051] Step 2: Soak the activated carbon fiber obtained in step 1 in a mixed solution of copper nitrate and thiourea dissolved in anhydrous ethanol, wherein the concentration of copper ions in the solution is 0.05 mol / L and the concentration of thiourea is 0.02 mol / L. The length of the water tank containing the solution should meet the carbon fiber passing time of 5 min, and then dry it in a 65°C oven;

[0052] Step 3: The carbon fiber loaded with the catalyst precursor obtained in step 2 is fed into a first tubular furnace sealed at both ends with nitrogen and filled with a reducing atmosphere. The reducing atmosphere is a mixture of hydrogen with a flow rate of 0.3 L / min and nitrogen with a flow rate of 0.3 L / min. The furnace temperature is 350°C. The length of the core temperature zone in the tubular furnace should meet the carbon fiber passage time of 10 min.

[0053] Step 4: The catalyst-carbon fiber obtained in step 3 is sent into a second tubular furnace with nitrogen gas seals at both ends and filled with a deposition atmosphere. The deposition atmosphere is a mixture of acetylene with a flow rate of 0.1 L / min, hydrogen with a flow rate of 0.2 L / min, and nitrogen with a flow rate of 0.3 L / min. The furnace temperature is 650°C, and the length of the core temperature zone in the tubular furnace should meet the carbon fiber passage time of 10 min;

[0054] After the step 4 device, a receiving fiber machine is used to collect the obtained fibers, thereby obtaining a continuous bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement.

[0055] Example 2

[0056] The difference from Example 1 is that the concentration of copper ions in the mixed solution in step 2 is 0.03 mol / L.

[0057] Example 3

[0058] The difference from Example 1 is that the concentration of thiourea in the mixed solution in step 2 is 0.01 mol / L.

[0059] Example 4

[0060] The difference from Example 1 is that the furnace temperature in step 3 is 450°C.

[0061] Example 5

[0062] The difference from Example 1 is that the reducing atmosphere in step 3 only includes hydrogen with a flow rate of 0.6 L / min.

[0063] Example 6

[0064] The difference from Example 1 is that the furnace temperature in step 4 is 550°C.

[0065] Example 7

[0066] The difference from Example 1 is that the deposition atmosphere in step 4 is a mixture of acetylene with a flow rate of 0.15 L / min, hydrogen with a flow rate of 0.15 L / min, and nitrogen with a flow rate of 0.3 L / min.

[0067] Example 8

[0068] The difference from Example 1 is that the deposition atmosphere in step 4 is a mixture of acetylene with a flow rate of 0.3 L / min and hydrogen with a flow rate of 0.3 L / min.

[0069] Example 9

[0070] A continuous device is used to grow bamboo-like carbon nanotubes on the surface of pulp-free carbon fiber. In the following continuous steps, the traveling speed of the carbon fiber tow is set to 20 cm / min;

[0071] Step 1: The commercial T300 carbon fiber was treated at 450°C for 90 minutes to remove the slurry, and then continuously fed into the electrolytic cell, with a 5wt.% diammonium phosphate solution as the electrolyte, a graphite plate as the cathode, and a carbon fiber tow parallel to the graphite plate as the anode. The current intensity was 0.4A, and the carbon fiber passed through the cell for 80 seconds. After passing through the electrolytic cell, the fiber entered the clean water tank for washing, and then was dried in an oven at 80°C.

[0072] Step 2: Soak the activated carbon fiber obtained in step 1 in a mixed solution of copper chloride and thiophene dissolved in deionized water, wherein the concentration of copper ions in the solution is 0.05 mol / L and the concentration of thiophene is 0.03 mol / L. The length of the water tank containing the solution should meet the carbon fiber passing time of 5 min, and then dry it in an oven at 80°C;

[0073] Step 3: The carbon fiber loaded with the catalyst precursor obtained in step 2 is fed into a first tubular furnace sealed at both ends with nitrogen and filled with a reducing atmosphere. The reducing atmosphere is hydrogen with a flow rate of 0.5 L / min, the furnace temperature is 350°C, and the length of the core temperature zone in the tubular furnace should meet the carbon fiber passage time of 5 min;

[0074] Step 4: The catalyst-carbon fiber obtained in step 3 is sent into a second tubular furnace with nitrogen gas seals at both ends and filled with a deposition atmosphere. The deposition atmosphere is a mixture of methane with a flow rate of 0.3 L / min and hydrogen with a flow rate of 0.3 L / min. The furnace temperature is 700°C, and the length of the core temperature zone in the tubular furnace should meet the carbon fiber passage time of 5 minutes;

[0075] After the step 4 device, a receiving fiber machine is used to collect the obtained fibers, thereby obtaining a continuous bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement.

[0076] Comparative Example 1

[0077] The difference from Example 1 is that the mixed solution in step 2 is replaced by an anhydrous ethanol solution dissolved with copper nitrate, and the concentration of copper ions in the solution is 0.05 mol / L.

[0078] Comparative Example 2

[0079] The difference from Example 1 is that the mixed solution in step 2 is replaced by an anhydrous ethanol solution dissolved with cobalt nitrate and thiourea, and the concentration of cobalt ions in the solution is 0.05 mol / L and the concentration of thiourea is 0.02 mol / L.

[0080] Comparative Example 3

[0081] The difference from Example 1 is that the mixed solution in step 2 is replaced by an anhydrous ethanol solution dissolved with cobalt nitrate, and the concentration of cobalt ions in the solution is 0.05 mol / L.

[0082] Comparative Example 4

[0083] The difference from Example 1 is that the mixed solution in step 2 is replaced by an anhydrous ethanol solution in which nickel nitrate is dissolved, and the concentration of nickel ions in the solution is 0.05 mol / L.

[0084] Comparative Example 5

[0085] The difference from Example 1 is that the furnace temperature in step 4 is 400°C.

[0086] Comparative Example 6

[0087] The difference from Example 1 is that the furnace temperature in step 4 is 800°C.

[0088] Table 1 is a comparison table of mechanical property test data of continuous multi-scale reinforcement prepared in the embodiments and comparative examples described in this application.

[0089] Table 1

[0090]

[0091] Table 2 is a comparison table of the microstructures of the continuous multi-scale reinforcements prepared in the embodiments and comparative examples described in this application.

[0092] Table 2

[0093] Preparation method Microstructure and distribution Linear density(g / m) Example 1 Bamboo-shaped carbon nanotubes; uniform and dense 0.913 Example 6 Bamboo-shaped carbon nanotubes; uniform and dense 0.853 Comparative Example 1 Bamboo-like carbon nanotubes + amorphous carbon clusters; uniform and sparse 0.789 Comparative Example 2 Carbon nanotubes + carbon nanowires + amorphous carbon clusters; dense clusters 0.903 Comparative Example 3 Carbon nanowires + amorphous carbon clusters; sparse and uneven 0.795 Comparative Example 4 Carbon nanowires + amorphous carbon clusters; dense clusters 0.947 Comparative Example 5 Carbon nanowires; uniform and sparse 0.803 Comparative Example 6 Bamboo-shaped carbon nanotubes; uniform and dense 0.868

[0094] Table 3 is a comparison table of test data of the surface structure of continuous multi-scale reinforcements prepared in the embodiments and comparative examples described in this application.

[0095] Table 3

[0096] Preparation method <![CDATA[Raman spectrum I D / I G > <![CDATA[Specific surface area (m 2 / g)]]> Example 1 0.71 18.75 Example 6 0.73 15.72 Comparative Example 1 0.77 5.21 Comparative Example 2 0.86 12.57 Comparative Example 3 0.88 4.67 Comparative Example 4 1.02 9.15 Comparative Example 5 0.79 7.16 Comparative Example 6 0.75 12.41

[0097] from Figure 1 It can be seen that the preparation method of the present invention successfully grows uniformly distributed bamboo-shaped carbon nanotubes on the surface of carbon fiber. Figure 1 A It can be seen that these carbon nanotubes completely cover each carbon fiber; Figure 1 B It can be seen that these carbon nanotubes generally have a bamboo-like structure.

[0098] As can be seen from Table 1, the continuous bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement obtained by the preparation method of the present invention is significantly superior to the continuous multi-scale reinforcement prepared by the prior art represented by Comparative Examples 1-4 in terms of interlaminar shear strength of the composite material, and at the same time maintains a high single-filament tensile strength, close to or even exceeding the standard strength of T700 grade carbon fiber (~4.90GPa). Compared with Example 1, Example 6 adopts a lower growth temperature, so Table 2 shows that its bamboo-shaped carbon nanotube production is lower than that of Example 1, but because the temperature used is low, the strength damage factor of carbon fiber is weakened, so its single-filament tensile strength is higher in Table 1. Comparative Examples 5 and Comparative Examples 6 are respectively the cases when the growth temperature is too low or too high. Although the too low growth temperature is beneficial to the strength of carbon fiber, its product is not bamboo-shaped carbon nanotubes, but carbon nanowires with poor strength, so the interface strength is low; although the too high growth temperature can still grow bamboo-shaped carbon nanotubes, the strength of carbon fiber is severely damaged, resulting in extremely low mechanical properties.

[0099] from Figure 2 As shown in Table 2, the carbon nanotubes grown on the carbon fiber surface by the preparation method of the present invention generally have a bamboo-like structure and are evenly and abundantly distributed on the carbon fiber surface. As shown in Table 2, the graphitization degree is significantly higher than that of the comparative examples (I D / I G The lower the value, the higher the degree of graphitization). Comparative Examples 1 and 6 have similar degrees of graphitization because their products are also bamboo-like carbon nanotubes. Figure 2 B and Table 2 show that the number of carbon nanotubes grown in Comparative Example 1 is small, accompanied by some amorphous carbon impurities, because the catalyst lacks sulfur promoter. Compared with copper-sulfur catalysts, the catalytic efficiency of pure copper catalysts is low, and the large-sized particles therein are easily coated by deposited carbon to form large amorphous structures. From the comparison of specific surface areas in Table 2, it can be seen that the low yield of carbon nanotubes leads to a small bonding surface between the carbon nanotubes and the resin matrix, which is not conducive to interface strengthening.

[0100] Combination Figure 2C and Table 3 show that the carbon nanotubes in the carbon nanotube-carbon fiber prepared in Comparative Example 2 are too densely distributed, and contain a large number of carbon nanowires and amorphous carbon impurities. These structures are filled in the middle of the carbon nanotube network, reducing the specific surface area, contributing less to interface strengthening, and even hindering the mutual bonding of resin and fiber. Combined with Tables 2 and 3, the carbon nanotubes grown in Comparative Example 3 are less and uneven, with a very low degree of graphitization, and are mixed with clusters of amorphous carbon impurities. The significantly reduced carbon nanotube yield compared with Comparative Example 2 is due to the lack of sulfur accelerator. Therefore, Table 1 shows that the interface performance of the multi-scale reinforcement prepared by it is very poor. The use of cobalt catalysts also further exacerbates the damage to the strength of carbon fibers caused by high temperatures, so its single-filament tensile strength is also very poor. Although the carbon nanotube-carbon fiber prepared in Comparative Example 4 has a large carbon nanotube yield, it has a poor degree of graphitization and is accompanied by a large number of amorphous carbon impurities. Therefore, although its carbon fiber strength has been strongly repaired, its specific surface area is low, so it cannot be fully combined with the resin, which is the reason for its poor interface performance.

[0101] From the above information, it can be seen that the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared by Example 1 has excellent microstructure and outstanding mechanical properties. In the preparation method, the main component copper in the catalyst and the promoter sulfur should have appropriate content and proportion, and the temperature and airflow in the CVD process should also be adjusted according to the optimized value. The use of copper catalyst can avoid the generation of amorphous carbon impurities and ensure the stable preparation of bamboo-shaped carbon nanotubes; the use of sulfur promoter can effectively improve the catalytic efficiency of the catalyst; too low growth temperature will also lead to the failure of bamboo-shaped carbon nanotubes to form; too high growth temperature will seriously damage the strength of carbon fiber. Therefore, the preparation method of the present invention can effectively solve the problems of unstable structure and uneven distribution of carbon nanotubes in the carbon nanotube-carbon fiber multi-scale reinforcement prepared by the prior art, and the difficulty of balancing high yield and associated impurities. The prepared continuous bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement can effectively improve the interface bonding of composite materials, thereby preparing high-performance carbon fiber composite materials suitable for a variety of advanced technology fields.

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement, characterized in that: include: The continuous carbon fibers are electrochemically treated to obtain surface activated carbon fibers; The surface-activated carbon fibers are continuously introduced into a mixed solution containing a copper salt and a sulfur source, followed by drying to obtain continuous carbon fibers with the copper salt and the sulfur source loaded on the surface; The continuous carbon fiber with copper salt and sulfur source loaded on the surface is subjected to thermal reduction treatment in a first tubular furnace filled with hydrogen to form a copper-sulfur catalyst in situ on the surface of the carbon fiber, thereby obtaining a continuous carbon fiber loaded with the copper-sulfur catalyst; The continuous carbon fiber loaded with copper-sulfur catalyst is passed through a second tubular furnace filled with hydrogen and a carbon source, wherein the temperature of the second tubular furnace is set to 500-700°C, and bamboo-shaped carbon nanotubes are in situ grown on the surface of the carbon fiber by chemical vapor deposition, thereby obtaining; The copper salt is copper chloride or copper nitrate; the sulfur source is thiourea or thiophene; the solvent of the mixed solution is deionized water, ethanol or acetone; The concentration of copper ions in the mixed solution is 0.02-0.08 mol / L, and the concentration of sulfur atoms is 0.01-0.05 mol / L.

2. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 1, characterized in that: The continuous carbon fiber is pulp-free or de-slurried commercial carbon fiber, the number of monofilaments in the commercial carbon fiber tow is 1K, 3K, 6K or 12K, and the specification of the commercial carbon fiber is T300, T700 or T800.

3. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 1, characterized in that: The electrochemical treatment is continuously carried out in an electrolytic cell with a graphite electrode as a cathode, continuous carbon fiber as an anode and ammonium dihydrogen phosphate solution as an electrolyte.

4. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 3, characterized in that: The electrolyte used in the electrochemical treatment is a 3-8wt.% ammonium dihydrogen phosphate deionized water solution, the current intensity is 0.1-0.5A, and the continuous carbon fiber passes through the electrolytic cell for 50-200s.

5. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 1, characterized in that: The first tubular furnace is open at both sides to allow carbon fibers to continuously pass through the furnace. Nitrogen gas flow is used at both ends of the first tubular furnace to block air outside the furnace, and a mixed flow of nitrogen and hydrogen is filled inside; or, a hydrogen gas flow is filled inside.

6. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 5, characterized in that: The temperature of the first tube furnace is set to 200-500°C, and the flow ratio of nitrogen and hydrogen in the furnace is 0-3:

1.

7. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 1, characterized in that: The second tubular furnace is open on both sides to allow carbon fibers to continuously pass through the furnace. Nitrogen gas flow is used at both ends of the second tubular furnace to block the air outside the furnace, and the interior is filled with a mixed gas flow of nitrogen, hydrogen and a carbon source; or, the interior is filled with a mixed gas flow of hydrogen and a carbon source; the carbon source is any one or more of methane, acetylene, carbon monoxide or gaseous ethanol.

8. The continuous preparation method of bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 7, characterized in that: The carbon source is acetylene, and the flow ratio of nitrogen, hydrogen and acetylene in the furnace is 0-6:0.5-3:

1.

9. A bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement prepared by the preparation method according to any one of claims 1 to 8.

10. A composite material, characterized in that: It comprises the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement as described in claim 9.

11. Application of the bamboo-shaped carbon nanotube-carbon fiber multi-scale reinforcement according to claim 9 or the composite material according to claim 10 in the preparation of military equipment, aerospace, sports goods, industrial equipment, infrastructure, ships and vehicles, and new energy components.

Citation Information

Patent Citations

  • Technique for catalytic growth of CNTs (carbon nanotubes) on surface of PAN-based carbon fiber on basis of sulfur-doped modified catalyst

    CN109763319A

  • KR20190115666A